2022
DOI: 10.1111/ijcs.12776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mixed bundling type on consumers’ value perception

Abstract: A discount through bundling can harm consumers’ perception of the reference price of, and willingness to pay for, the bundled products. This study investigates how types of bundling such as mixed‐leader and mixed‐joint bundling affect the value perception of a primary product. Three experiments were developed and used to test theoretical hypotheses. Data were collected and analyzed using multivariate analyses of variance and mediation analysis with the bootstrapping procedure. Results show that leader bundling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The purpose of promotion is to increase the value of a product or service in consumers' minds (Kotler & Keller, 2006), which includes both the acquisition value (i.e., the net gains derived from the product or service acquired) and the transaction value (i.e., the level of satisfaction or pleasant feeling derived from a transaction or the feeling obtained from getting a good price) (Cai et al, 2016; Grewal et al, 1998). Only when consumers recognize the value in the promotion activities and make sure that they can obtain benefits from it will they take actual purchase actions (Li & Song, 2022; Monroe, 1973; Peng & Liang, 2013). In addition, Raghubir et al (2004) stated that consumers respond to promotions favourably because of the positive benefit perceptions that the promotions bring to them, which allow consumers to perceive higher values (Peng & Liang, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The purpose of promotion is to increase the value of a product or service in consumers' minds (Kotler & Keller, 2006), which includes both the acquisition value (i.e., the net gains derived from the product or service acquired) and the transaction value (i.e., the level of satisfaction or pleasant feeling derived from a transaction or the feeling obtained from getting a good price) (Cai et al, 2016; Grewal et al, 1998). Only when consumers recognize the value in the promotion activities and make sure that they can obtain benefits from it will they take actual purchase actions (Li & Song, 2022; Monroe, 1973; Peng & Liang, 2013). In addition, Raghubir et al (2004) stated that consumers respond to promotions favourably because of the positive benefit perceptions that the promotions bring to them, which allow consumers to perceive higher values (Peng & Liang, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Qiang et al (2021) considered mixed‐leader bundling and explored whether the types of bundling strategies differed depending on the similarity of the products. Li and Song (2022) took mixed‐leader bundling into account and investigated how different bundling strategies influence the perceived value of the main product. Gayer et al (2021) compared the profitability of implementing sequential bundling, pure bundling, and mixed bundling with no bundling and showed that the sequential bundling strategy yields higher profits.…”
Section: Literature Reviewmentioning
confidence: 99%